2011
DOI: 10.5194/acp-11-11497-2011
|View full text |Cite
|
Sign up to set email alerts
|

Mass absorption efficiency of elemental carbon and water-soluble organic carbon in Beijing, China

Abstract: The mass absorption efficiency (MAE) of elemental carbon (EC) in Beijing was quantified using a thermal-optical carbon analyzer. The MAE measured at 632 nm was 8.45&plusmn;1.71 and 9.41&plusmn;1.92 m<sup>2</sup> g<sup>−1</sup> during winter and summer respectively. The daily variation of MAE was found to coincide with the abundance of organic carbon (OC), especially the OC to EC ratio, perhaps due to the enhancement by coating with organic aerosol (especially secondary organic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
200
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(240 citation statements)
references
References 83 publications
(103 reference statements)
26
200
6
Order By: Relevance
“…Thus, relatively higher b abs at Allahabad are attributed to the higher EC mass concentrations. The σ abs values, obtained in the present study, are relatively higher compared to those reported over Chinese regions; for example 7.7 m 2 /g (in PM 2.5 samples collected at urban Guangzhou) (Andreae et al, 2008), 9.3 ± 1.4 m 2 /g (for PM 1.0 ) at urban Xinken (Cheng et al, 2008) and 8.45 ± 1.7 m 2 /g for aerosol over Bejing during wintertime (Cheng et al, 2011). There is a lack of scattering coefficient (b scat ) measurements over northern India.…”
Section: Chemical and Absorption Properties Of Aerosol During Clear Dcontrasting
confidence: 38%
“…Thus, relatively higher b abs at Allahabad are attributed to the higher EC mass concentrations. The σ abs values, obtained in the present study, are relatively higher compared to those reported over Chinese regions; for example 7.7 m 2 /g (in PM 2.5 samples collected at urban Guangzhou) (Andreae et al, 2008), 9.3 ± 1.4 m 2 /g (for PM 1.0 ) at urban Xinken (Cheng et al, 2008) and 8.45 ± 1.7 m 2 /g for aerosol over Bejing during wintertime (Cheng et al, 2011). There is a lack of scattering coefficient (b scat ) measurements over northern India.…”
Section: Chemical and Absorption Properties Of Aerosol During Clear Dcontrasting
confidence: 38%
“…It has also been proposed that atmospheric heating as a result of EC may affect large-scale circulation and the hydrological cycle, leading to significant regional climate effects (Cheng et al, 2011). Typically, EC is treated as the only light-absorbing species in climate models (Kirchstetter et al, 2004;Cheng et al, 2011). However, the effects of light-absorbing organic brown carbon, or BrC, are becoming more apparent and have been reported at 28% of total absorption at lower wavelengths for California (Doherty et al, 2010;Bahadur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among atmospheric pollutants it is second only to CO 2 in potential forcing (Bond et al, 2013). It has also been proposed that atmospheric heating as a result of EC may affect large-scale circulation and the hydrological cycle, leading to significant regional climate effects (Cheng et al, 2011). Typically, EC is treated as the only light-absorbing species in climate models (Kirchstetter et al, 2004;Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the MAEs of EC at 632 nm of coal and biomass burning (wheat and rape straws) in this study were 5.6 ± 0.3 and 5.5 ± 0.6 m 2 g −1 , respectively. Moreover, the MAEs of EC at 632 or 650 nm of diesel, biomass burning sources (e.g., crop residual and wood) and coal combustion reported in previous studies ranged from 3.0 to 8.4 m 2 g −1 (Cheng et al 2011;Shen et al 2013). It can be easily seen that the MAEs of EC from source samples were much lower than those obtained in ambient aerosols.…”
Section: Mae Of Ec In Pm 25mentioning
confidence: 77%
“…To compare with other cities, the MAEs of EC at 632 nm were estimated according to AAEs for all seasons in Chengdu. The MAEs of EC were 9.1, 9.7, 9.1 and 9.4 m 2 g −1 , respectively, in spring, summer, autumn and winter, which were slightly higher than those measured in summer (9.4 m 2 g −1 ) and winter (7.5-8.5 m 2 g −1 ) in Beijing (Cheng et al 2011;Wu et al 2016). In fact, the MAEs of EC at 632 nm of coal and biomass burning (wheat and rape straws) in this study were 5.6 ± 0.3 and 5.5 ± 0.6 m 2 g −1 , respectively.…”
Section: Mae Of Ec In Pm 25mentioning
confidence: 78%